Σύγκριση εναλλακτικών μεθόδων ανάλυσης και σχεδιασμού μεταλλικών πλαισίων - Σκιαδόπουλος, Ανδρόνικος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Μεταλλικών Κατασκευών, 2016)
The primary objective of this thesis is to examine the alternative methods of analysis and design of steel frames and structures. Some of the issues treated include the limits that allow for first order analysis, the impact of material in plastic analysis and the kind of analysis and design that should be applied in each case, both for plane frames and realistic three dimensional steel structures. Furthermore, this thesis also examines the cases in which imperfections should be incorporated in the analysis, the differences between alternative ways of imperfections’ consideration, as well as what the most unfavourable direction of both global and local imperfections is. In determining the limits that differentiate each analysis and design method and generally in exploring the aforementioned issues, structures of diverse slenderness should be examined. The need for comparable results among all structures led to analyses of structures of identical cross-sections, geometry and dimensions. Consequently, their distinctive characteristic in the parametric analyses is the external loading which is chosen so that it leads the structure to its ultimate limit state (ULS) according to plastic analysis (GMNIA). Hence, it is feasible to create a satisfying spectrum of structures’ slenderness of comparable results. In the first chapter, an introduction in the necessity of second order analysis in some cases of steel structures is presented. Additionally, the impact that imperfections may have in specific occasions in structures is also highlighted. Finally, briefly insights into the objective and scope of each upcoming chapter are also introduced. In the second chapter, the main scope is the evaluation and the comparison of the different proposals of Eurocode 3. For that reason, plastic parametric analyses with all possible imperfections are applied for the entire spectrum of structures according to the current version of EC3. In particular, the primary purpose is to determine whether the condition acr>15 that allows for first order analysis is accurate. Furthermore, thorough insights into the impact of each proposed method of taking into account imperfections are given. Among others, the most unfavourable direction of imperfections, the difference between geometrically applied imperfections and applying equivalent forces and the impact of material on varying structures, are all topics examined in this thesis. Moreover, an extensive methodology related to how imperfections in the shape of the critical elastic buckling mode are applied in structures is introduced in this chapter. Due to the need for comparable results, external loads are chosen in every case so that the multiplying collapse factor of the structure is λ=1. In the third chapter, elastic parametric analyses with the same external loads as before are applied to the structures according to the revised version of Eurocode 3. The aim of this chapter is the evaluation of the proposed method of analysis and design for each structure of the spectrum. To achieve this goal, every structure is analysed and verified with every possible method and, lastly, the most appropriate one is suggested. If that method is different than the proposed one, a revision will be required. Additionally, results of both Eurocode 3 and linear buckling analysis (LBA) regarding the member buckling verification and results of plastic and elastic analysis are also compared in this chapter. Due to inconsistencies in the results of the previous chapter and the proposed methods of Eurocode 3 that are attributed to out-of-frame’s-plane effects, the fourth chapter examines all proposed methods in a realistic three-dimensional structure. In that way, it is possible to determine whether the simplified frame structure of the second and third chapter produced reliable results. In order for the results of each chapter to be comparable, the external loading in this case is also identical to the previous structures’ loading with the difference that out-of-frame’s-plane horizontal forces are added in the analysis so that out-of-plane effects are taken into consideration. Finally, in the fifth and final chapter, final remarks and conclusions of the diploma thesis are presented, and suggestions for further investigation in the field of methods of analysis and design of steel structures are suggested.